(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research is to design and construct the practical field test to measure the rapidity of motion response of the emerging football players and to identify the nature of the measurement of this important motor ability. The aim of the research is to identify the possibility of the test designed by the researchers in measuring the rapidity of motion response The researchers used the descriptive method and formed the research sample (from 60 players) and the percentage of the research sample (100%) of the original research community. And the most important findings of the researchers that the test designed for the rapidity of motion response of young footballers can distinguish between the testers، and concluded that any test that succeeds in combining the mathematical laws and the practical situation is more accurate and careful of the tests judged by personal experience or viewing ، The researchers recommended the use of the test by professionals، specialists and researchers in the field of sports in general to know the level of players in the training، in addition to the need to conduct other research on the rapidity of motion response of the other games، which is of paramount importance in the development of athletes، especially young people